THERMOMECHANICAL PROCESSING OF CHROMOMOLIBDENUM ROLLING IN THE CONDITIONS OF JSC BMZ – MANAGEMENT COMPANY OF HOLDING BMK - V. A. Lutsenko; T. N. Golubenko; O. V. Lutsenko; P. A. Bobkov; L. A. Drobyshevsky (Литьë и металлургия)
It is shown that after thermo-mechanical processing of chrome-molybdenic rolled metal including cooling with a speed of 0,6-0,8 ° C / sec, the quantity of bainite increases to 75% and the amount of lamellar pearlite decreases to 5-10% in structure that promotes reduction of the mode of subsequent softening processing. It is established that at cooling with a specified speed the transformations in chrome-molybdenic steel come to an end at temperatures of 350-370 ° C. The offered technology of the reduced mode of thermomechanical processing provides necessary quality of rolled metal and promotes decrease of energy resources consumption.